REALIZATION OF ROOT VARIATIONS VOROB- AND HOROB- IN SLAVONIC ANTHROPONYMY - Yatsiy, V. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with peculiarities of realization some root variations вороб-, гороб- and also their derivatives in Slavonic personal names. In accordance with the anthroponymic derivatives their motivational features are established, phonetic and grammatical modifications and word-formation models of anthroponym derivatives are researched. Various aspects of research give the opportunity to prove following statement: onomastics of any territory is connected with the linguistic features of the region.